The New Technology for In Vitro Culture with Induction of Nanobubbles (NBsN2 and NBsO2) in Cattleya sp. - Mustakim, Moch; Mawardi, Azis; Dewi, Lina Purnama; Putri, Nela Vede Rhofa; Rahayu, Tintrim; Jayanti, Gatra Ervi (Biology, Medicine, & Natural Product Chemistry, 2024)
The growth and development of orchids take a relatively long time, while the demand for high-quality orchids continues to increase significantly. Tissue culture is a technique of isolating plant parts in organs, tissues, and cells and then culturing these plants on artificial media in a sterile environment. Tissue culture techniques can reproduce plants in a relatively short time, with the same properties and quality, so efforts to optimize tissue culture with technology are the right solution, one of which is using nanogenerator technology that produces Nanobubbles (NBs). NBs are one of the nanotechnologies that are ?100 nm in size with induced gas needed by plants. This study aims to determine the effectiveness of growth and development from the induction of NBsN2 and NBsO2 in Cattleya sp. planlet in vitro culture. This research method uses in vitro culture with a Randomized Group Design. The results of the MsO treatment showed higher weight than other treatments, with a total plant weight value of 0.3550 g and a total plant height value of 1.3983 cm. Murashige-Skoog + NBsNitrogen (MsN) treatment showed higher root length than other treatments with a total value of 1.2367 cm. In the treatment of Ms, MsO, OJ and NJ, a live percentage of 83-100% was observed. The statistical test results indicate that NBs positively affect Cattleya sp. plantlets. This effect includes increasing plant weight, height, and root length and promoting new shoots growth. Additionally, nitrogen supplements play a role in colour changes, indicating the plant's health and photosynthetic efficiency. In the treatment with Induction O2, the initial colour changes from Strong Yellow Green (141 D) to Strong Yellowish Green (141 C), while in the treatment with Induction NBsN2, the initial colour changes from Strong Yellow Green (141 D) to Deep Yellow Green (141 B).